Experimental investigation of a powered lifting assistance device introducing direct touch between the caregiver and the care receiver - Mari Kurata; Ming Jiang; Kotaro Hoshiba; Yusuke Sugahara; Takahiro Uehara; Masato Kawabata; Ken Harada; Yukio Takeda (Frontiers in Bioengineering and Biotechnology)
IntroductionTransferring a patient from one place to another is one of the most strenuous works in nursing care. To address this issue, we proposed a concept for a lifting assistance device that uses two cables to perform operations such as translation, rotation, and stay. It facilitates direct touch between the caregiver and the care receiver, allowing intuitive adjustments of position and posture based on the caregiver’s intention, detected through variations in cable tension.MethodsTo investigate the effectiveness of this concept, lifting experiments using a fabricated prototype were conducted. Twelve subjects, including four physical therapists (PTs) and eight subjects having no transfer experience, acted as caregivers, and a dummy was used as the care receiver.ResultsResults show that regardless of the transfer experience, the caregiver’s intention detection and adjustment of the care receiver’s position and posture were successfully achieved with an accuracy of over 70%.DiscussionSurvey feedback collected after the lifting experiments confirmed that utilizing direct touch between the caregiver and the care receiver was highly valued by all subjects, with a 5-point Likert scale rating both PTs (average score: 4.8 points) and non-experienced subjects (average score: 4.3 points).